STRATEGI MANAJEMEN DALAM MEMPERTAHANKAN EKSISTENSI PROGRAM SIARAN DUNIA DONGENG DI RRI PURWOKERTO - Ari Mintarti Murbaningsih; Purwanto; Ade Wahyudin (Program Studi Ilmu Komunikasi, 2020)
Abstract:RRI Purwokerto is a public broadcasting institution that must be able to serve his audience. Broadcasting media management which is implemented in LPP RRI Purwokerto based on vision and mission is reflected in each radio program. One of the Programs in LPP RRI is Dunia Dongeng. The program is carried by a storyteller who reads a story with many characters. The purpose of the research is to determine the management strategies to maintain the existence of the Dunia Dongeng program in LPP RRI Purwokerto using SWOT Analysis. According to SWOT Analysis, there is a lot of strength and opportunities such as the storyteller is a professional and the audience segmentation is kid community. The content quality of the story is good and meaningful. The time of broadcast is determined according to the needs of the audience. Interesting and varied presentation. The analysis result can become a recommendation to improve the quality and quantity of the audience.